THE STUDENTS' DIFFICULTIES IN WRITING DESCRIPTIVE TEXT AT THE TENTH-GRADE STUDENT OF SMK N 4 JAMBI IN ACADEMIC YEARS 2022/2023 - Adla, Sheyla Halimatul (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
The purpose of this research is to find out students' difficulties in writing descriptive text. The problem of this research is students' difficulties in generic structure, language features, lack of vocabulary and arranging sentences in writing descriptive text. The objective of this research is to identify the students' difficulties in writing descriptive text. The research was conducted at SMK N 4 Jambi in the academic year 2022/2023. The population of this research is tenth-grade student of fashion class IV. The sample is all of the fashion class IV at the tenth grade and the total number of students is 33 female students. The type of research is qualitative descriptive. The data were obtained by using an online questionnaire by using google forms. Overall, the result of this research is 51% of students have difficulties with language features. While, 57% of students have difficulties in generic structure, which is the same as those who have limited vocabulary in writing descriptive text. Moreover, the biggest percentages are the majority of students have difficulties in arranging sentences to be paragraphs. Keywords; students' difficulties, writing descriptive text